2019
DOI: 10.1093/mnras/stz3198
|View full text |Cite
|
Sign up to set email alerts
|

THOR 42: A touchstone ∼24 Myr-old eclipsing binary spanning the fully-convective boundary

Abstract: We present the characterization of CRTS J055255.7−004426 (=THOR 42), a young eclipsing binary comprising two pre-main sequence M dwarfs (combined spectral type M3.5). This nearby (103 pc), short-period (0.859 d) system was recently proposed as a member of the ∼24 Myr-old 32 Orionis Moving Group. Using ground-and space-based photometry in combination with medium-and high-resolution spectroscopy, we model the light and radial velocity curves to derive precise system parameters. The resulting component masses and… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 100 publications
(162 reference statements)
1
6
0
Order By: Relevance
“…Similar differences between these PHOENIX and BT-Settl model atmospheres have also been found in other studies of young, low-mass EBs, e.g. Murphy et al (2020) found that the PHOENIX models gave effective temperatures which were ∼30 K cooler in their study of a ∼24 Myr-old system, whilst Gillen et al (2020a) found temperatures to be cooler by ∼160 K and ∼125 K for the two <10 Myr-old systems analysed therein. The effect of the lower temperatures and luminosities in the context of stellar evolution models is illustrated in Figure 9, where the black crosses in the HRDs are shifted down and to the right, relative to the main results.…”
Section: Differences Between Using Bt-settl and Phoenix Atmosphere Mo...supporting
confidence: 84%
See 2 more Smart Citations
“…Similar differences between these PHOENIX and BT-Settl model atmospheres have also been found in other studies of young, low-mass EBs, e.g. Murphy et al (2020) found that the PHOENIX models gave effective temperatures which were ∼30 K cooler in their study of a ∼24 Myr-old system, whilst Gillen et al (2020a) found temperatures to be cooler by ∼160 K and ∼125 K for the two <10 Myr-old systems analysed therein. The effect of the lower temperatures and luminosities in the context of stellar evolution models is illustrated in Figure 9, where the black crosses in the HRDs are shifted down and to the right, relative to the main results.…”
Section: Differences Between Using Bt-settl and Phoenix Atmosphere Mo...supporting
confidence: 84%
“…These systems ought to be especially stringent tests of stellar evolution models because, as well as having well-determined parameters and ages, different physics are relevant to each component, plus the low mass ratios are good tests of model isochrone gradients. Interestingly, in these cases we have two systems-those in Praesepe (Gillen et al 2017) and the 32 Orionis moving group (Murphy et al 2020)-where the masses and radii of both components agree well with (non-magnetic) model predictions, and another two systems-in Blanco 1 (this work) and NGC 1647 (Hebb et al 2006)-where it is the higher-mass component that appears to be inflated (although the secondary in NGC 647 is smaller than expected for its assumed cluster age of 150 Myr). Three out of these four systems (not Praesepe) also have very short periods (∼1 day), meaning that they will be fast rotators (assuming spin-orbit synchronisation) and hence would be expected to exhibit enhanced magnetic activity.…”
Section: The Fully Convective Boundarymentioning
confidence: 97%
See 1 more Smart Citation
“…Taking a ∼0.75 mag offset into account due to binarity, TOI 507 still sits slightly above the main sequence, meaning that it remains a potentially young touchstone system amenable to characterisation as in e.g. Murphy et al (2020). The mass, radius, 𝑚 bol , and flux reported in Table 2 have been derived for a single component of this binary system, assuming equal mass and brightness.…”
Section: Emission Features In Tess Candidatesmentioning
confidence: 99%
“…However, MacDonald & Mullan (2021) found that the binary is older than the 32 Ori association when the physical parameters of its components were interpreted with evolutionary models that include magnetic effects. That study also closely compared the UVW data for THOR 42 from Murphy et al (2020) and the velocities for other proposed members of 32 Ori, concluding that the kinematics of THOR 42 may provide additional evidence of nonmembership. THOR 42 was not selected as a candidate member of 32 Ori in Section 2 because it is slightly beyond the decl.…”
Section: Rodriguezmentioning
confidence: 59%